Una reflexión sobre el método Arco-Genealógico (2019)
Este artículo pretende aproximar algunas reflexiones sobre el método que emerge de la propuesta foucaultiana. Se alude a la labor metódica en línea de la comprensión kantiana de Foucault en tanto ontología histórico crítica del presente, al momento que se marca su crítica no normativa como labor de ficcionalización. Del mismo modo, se indica cómo las categorías de eventualización y problematización van sobre la singularidad y contingencia de las prácticas discursivas y no discursivas. Posteriormente, se dan algunas pistas sobre la arqueología, luego, sobre la genealogía y ulteriormente sobre su funcionamiento entrelazado. El artículo concluye mostrando la potencia que puede tener el método foucaultiano para analizar aquellas subjetividades que se construyen en medio de dispositivos contemporáneos de poder-saber. Abstract: Located in the post- structuralist current, this article aims to bring some reflections about the method that emerges from the Foucauldian proposal. Thus, the spotlight is put on the categories and concepts which have been fundamental on Foucault’s work from the archaeology and genealogy, in order to think about a coherent epistemological approach on certain objects of study that are allowed to be analyzed by it. The methodical task is referred as follows: it is consistent with the Kantian grasp of Foucault ascriticalhistoricalontologyof the present, at the moment of marking his nonregulation critic as a chore of fictionalization. Similarly, it is shown how the eventualization and problematization categories match with the uniqueness and possibility of discursive and non-discursive practices. Subsequently, some clues about archaeologyare given, then on the genealogy, and afterwards, about its crossed functioning. At the end, it is shown what the power of the Foucauldian method can have in order to analyze those subjectivities which are constructed through contemporary devices of power- knowledge.